The SocioBox: A Novel Paradigm to Assess Complex Social Recognition in Male Mice - Krueger-Burg, Dilja; Winkler, Daniela; Mitkovski, Mišo; Daher, Fernanda; Ronnenberg, Anja; Schlüter, Oliver M.; Dere, Ekrem; Ehrenreich, Hannelore (Frontiers in Behavioral Neuroscience, 2016)
Impairments in social skills are central to mental disease, and developing tools for their assessment in mouse models is essential. Here we present the SocioBox, a new behavioral paradigm to measure social recognition memory. Using this paradigm, we show that male wildtype mice of different strains can readily identify an unfamiliar mouse among 5 newly acquainted animals. In contrast, female mice exhibit lower locomotor activity during social exploration in the SocioBox compared to males and do not seem to discriminate between acquainted and unfamiliar mice, likely reflecting inherent differences in gender-specific territorial tasks. In addition to a simple quantification of social interaction time of mice grounded on predefined spatial zones (zone-based method), we developed a set of unbiased, data-driven analysis tools based on heat map representations and characterized by greater sensitivity. First proof-of-principle that the SocioBox allows diagnosis of social recognition memory deficits is provided using male PSD-95 heterozygous knockout mice, a mouse model related to psychiatric pathophysiology.